2015
DOI: 10.1007/s12031-015-0524-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the M1 Muscarinic Acetylcholine Receptor on Retinal Neuron Number Studied with Gene-Targeted Mice

Abstract: Pharmacological activation of the M1 muscarinic receptor subtype was suggested to promote the survival of retinal neurons. We examined the hypothesis that the M1 receptor is crucial for retinal neuron survival in vivo by using mice devoid of the M1 receptor gene. Muscarinic receptor gene expression was determined in the retina using real-time PCR. The amount of neurons in the retinal ganglion cell layer and of axons in the optic nerve was determined in retinal wholemounts stained with cresyl blue and in optic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In a previous study from our laboratory conducted on 5 month-old M1R−/− mice of a mixed genetic background, we found that neuron number in the RGC layer and optic nerve axon number were not affected by M 1 receptor deficiency 31 . One possible explanation for these findings was that the M1R−/− mice used in the previous study might have been too young to develop neuronal loss.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In a previous study from our laboratory conducted on 5 month-old M1R−/− mice of a mixed genetic background, we found that neuron number in the RGC layer and optic nerve axon number were not affected by M 1 receptor deficiency 31 . One possible explanation for these findings was that the M1R−/− mice used in the previous study might have been too young to develop neuronal loss.…”
Section: Discussionmentioning
confidence: 63%
“…In the retina, cholinergic amacrine cells are the source of the physiological muscarinic receptor agonist, acetylcholine, which was shown to transmit cholinergic signals to RGCs via muscarinic and nicotinic receptors 4043 . However, although multiple muscarinic receptor subtypes, including the M 1 receptor, were detected on RGCs, amacrine cells and bipolar cells, the specific role of the individual subtypes in retinal cell-to-cell signaling is still poorly understood 31,42 . Overlapping receptor subtype expression patterns in individual cell types, limited selectivity of pharmacological ligands and low specificity of antibodies for individual muscarinic receptor subtypes are obstacles in this regard 28,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, a retinal wholemount was prepared in cold PBS, transferred onto a glass slide, and stained with cresyl blue as previously described [29]. After the staining procedure, sixteen predefined areas per wholemount, eight central and eight peripheral, of 150 μ m × 200 μ m were photographed by a blinded investigator as reported in detail previously [25, 30, 31]. Per photograph, all cresyl blue-positive cells were counted manually by a blinded investigator using the cell counter plugin for ImageJ software (NIH, http://rsb.info.nih.gov/ij/) as previously described [25, 31].…”
Section: Methodsmentioning
confidence: 99%
“…After the staining procedure, sixteen predefined areas per wholemount, eight central and eight peripheral, of 150 μ m × 200 μ m were photographed by a blinded investigator as reported in detail previously [25, 30, 31]. Per photograph, all cresyl blue-positive cells were counted manually by a blinded investigator using the cell counter plugin for ImageJ software (NIH, http://rsb.info.nih.gov/ij/) as previously described [25, 31]. The mean cell density (cells/mm 2 ) was calculated and multiplied with the wholemounts' surface area to obtain the total number of cells per retina.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation